Evaluation of diagnostic potential of immunoreactive epitopes of the Omptin protease family by using a peptide library - V. A. Feodorova; M. A. Khizhnyakova; S. S. Zaitsev; A. M. Lyapina; L. V. Sayapina; E. P. Lyapina; O. V. Ulyanova; V. L. Motin (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The construction of highly sensitive new-generation diagnostic test systems requires the use of modern innovative technologies that are capable of detecting infectious agents at the molecular level by identifying specific antibodies to individual immunoreactive epitopes. The development of such immunoassays is based on molecular mapping of a target antigen using a library of short overlapping peptides aimed at identification of both epitopes specific for a particular pathogen, and those common to the group of infectious agents. The article describes new approaches that are based on the results of mapping of the Omptin group model protein that could be critical for improving retrospective laboratory diagnosis of infectious diseases caused by bacteria of the Enterobacteriaceae family. The article discusses the prospects for assessing the applicability of the peptide ELISA experimental version, designated as p6/24-Omptin-TIFA, for the detection of antibodies to diagnostically significant Omptin epitopes in the serum of people who have had enterobacterial infections, in order to introduce it into healthcare practices.